Apigenin remodels the gut microbiota to ameliorate ulcerative colitis - Fu, Rongrong; Wang, Lechen; Meng, Ying; Xue, Wenqing; Liang, Jingjie; Peng, Zimu; Meng, Jing; Zhang, Min (Frontiers in Nutrition, 2022)
Introduction Ulcerative colitis (UC), a chronic non-specific colorectal inflammatory disease with unclear etiology, has long plagued human health. Gut microbiota dysbiosis destroy homeostasis of the colon, which is closely related to ulcerative colitis progress. Apigenin, a flavonoid widely present in celery, has been found to improve ulcerative colitis. However, the potential molecular mechanism of apigenin ameliorating ulcerative colitis through protecting intestinal barrier and regulating gut microbiota remains undefined. Methods Dextran sodium sulfate (DSS)-induced colitis mouse model was conducted to evaluate the effect of apigenin on UC. Disease activity index score of mice, colon tissue pathological, cytokines analysis, intestinal tight junction proteins expression, and colonic content short-chain fatty acids (SCFAs) and 16S rRNA gene sequencing were conducted to reflect the protection of apigenin on UC. Results The results indicated that apigenin significantly relieved the intestinal pathological injury, increased goblet cells quantity and mucin secretion, promoted anti-inflammatory cytokines IL-10 expression, and inhibited the expression of proinflammatory cytokines, TNF-α, IL-1β, IL-6 and MPO activity of colon tissue. Apigenin increased ZO-1, claudin-1 and occludin expressions to restore the integrity of the intestinal barrier. Moreover, apigenin remodeled the disordered gut microbiota by regulating the abundance of Akkermansia, Turicibacter, Klebsiella, Romboutsia, etc., and its metabolites (SCFAs), attenuating DSS-induced colon injury. We also investigated the effect of apigenin supplementation on potential metabolic pathways of gut microbiota. Conclusion Apigenin effectively ameliorated DSS-induced UC via balancing gut microbiome to inhibit inflammation and protect gut barrier. With low toxicity and high efficiency, apigenin might serve as a potential therapeutic strategy for the treatment of UC via regulating the interaction and mechanism between host and microorganism.